Animal behaviour : evolution and mechanisms - Anthes, Nils. (Springer Berlin Heidelberg, 2010)
The study of animal behaviour is one of the fastest growing sub-disciplines in biology. The resulting diversity of conceptual approaches and methodological innovations makes it increasingly difficult for professionals and students to keep abreast of important new developments. This edited volume provides up-to-date reviews that facilitate orientation in key areas of animal behaviour, including communication, cognition, conflict, cooperation, sexual selection and behavioural variation. The contributions address evolutionary and proximate aspects of behaviour and also cover both invertebrates and vertebrates. Important concepts are dealt with in separate glossaries and key examples highlighted in separate text boxes. Richly illustrated with colour figures, this volume offers a well structured overview of all the main developments in current animal behaviour research. It is ideal for teaching upper-level courses, where it will be essential reading for advanced students familiar with basic concepts and ideas. Communication and cognition -- Visual communication: evolution, ecology, and functional mechanisms -- Vocal communication in social groups -- Kin recognition: an overview of conceptual issues, mechanisms and evolutionary theory -- Honeybee cognition -- Individual performance in complex social systems: the greylag goose example -- Conflict and cooperation -- Conflict and conflict resolution in social insects -- Social insects, major evolutionary transitions and multilevel selection -- Cooperation between unrelated individuals – a game theoretic approach -- Group decision-making in animal societies -- Parental care: adjustments to conflict and cooperation -- Sex and reproduction -- The quantitative study of sexual and natural selection in the wild and in the laboratory -- Mate choice and reproductive conflict in simultaneous hermaphrodites -- Extra-pair behaviour -- Extreme polyandry in social Hymenoptera: evolutionary causes and consequences for colony organisation -- Monogynous mating strategies in spiders -- Mating systems, social behaviour and hormones -- Behavioural variation -- The social modulation of behavioural development -- Alternative reproductive tactics and life history phenotypes -- Animal personality and behavioural syndromes -- Social learning and culture in animals -- Levels and mechanisms of behavioural variability.